Wybrane elementy zachowania pilkarzy noznych - Rychta, T. (Human Movement, 2001)
The subject of the research were the following elements of soccer players behavior: speed of perception, dimensions of deliberate behavior, activity control indices, sport motivation indices, and fear indices. Deliberate behavior theory by Z. Zaleski, activity control theory by J. Kuhl, and the personality concept by T. Madrzycki were assumed the basis for the research. The problem of the research can be presented within two questions: 1. Do players of two soccer teams representing a similar level of sport skills differ in the chosen elements of deliberate behavior? 2. What correlations can be observed in soccer players between the dimensions of deliberate behavior and the psychological variables under consideration? The hypothesis of the research were as follows: 1. Players of both teams present similar results concerning the chosen elements of behavior. 2. There are numerous statistically significant positive correlations among the soccer players' behavior elements under consideration. The following research tools were applied: 1. A modified version of Toulouse-Pieron attention test, consisting of three trials (S1 - one sign elimination; S2 - two signs elimination; S3 - three signs elimination) assessing the speed of perception. 2. Goal Questionnaire by Z. Zaleski, allowing for the assessment of the following dimensions of deliberate behavior: WAC (goal value), OCZ (expectation, the chance to achieve the goal), KOC (conflict of goals), WYSD (activity effort), WYTD (persistence in the activity), ZAD (satisfaction with the activity), and two interpersonal dimensions: WSPC (the community of the player's and the coach's goal) and WSPE (emotional relation between the player and the coach). 3. Activity Control Questionnaire by J. Kuhl. By means of this questionnaire, the activity/state orientation was measured in three sports situations: C (when taking an activity), N (after failure), and D (when planning an activity and taking the decision). 4. Sports Motivation Questionnaire by D.L. Gill and T.E. Deeter, measuring WSP (rivalry), MOTZ (motivation to win), and MOC (goal motivation). 5. Success Perception Questionnaire by G.C. Roberts and G. Balague, used to assess ORWS (rivalry orientation) and ORM (mastery orientation 6. Fear State and Features Inventory by C.D. Spielberg and other test aiming at the measurement of fear as a state (x-1) and fear as a feature (x-2). The total of 41 players were analyzed from two soccer teams (A - 22, B - 19). All of them aimed at playing in the 1st state league at the age of 18-36 years. The mean age equaled 26.07; the standard deviation was 4.12. The research leads to the conclusion that team A players presented only a higher average in the trial of two signs elimination: S2 (t =2.42, p < 0.02) and in the index of the community of the player's and the coach's goal: WSPC (t = 2.23, p < 0.03). Team B players, in turn, achieved better results only in the trial of three signs elimination: S3 (t = 4.06, p < 0.00) and in the index of goal conflict: KOC (t = 2.55, p < 0.01). As far as all other elements of soccer players' behavior are concerned, the differences between the averages of the two teams turned out statistically insignificant. For the whole group of soccer players (n = 41) r-Pearson correlation indices were calculated between dimensions of deliberate behavior and other variables under consideration. A few statistically significant correlations were stated. The goal value (WAC) correlated positively and statistically significantly with: the speed of perception (S2), rivalry orientation (ORWS), rivalry (WSP), motivation to win (MOTZ), and goal motivation (MOC). Expectation, in other words the chance to achieve the goal (OCZ), correlated positively and statistically significantly with rivalry and motivation to win. The community of the player's and the coach's goal (WSPC) and the emotional relation between the player and the coach (WSPE) correlated positively with rivalry (WSP). The results of the research conformed with the expectations concerning similar outcomes in both soccer teams. However, the results turned out different than the expectations concerning numerous positive correlations among the behavior elements under consideration. This means that, firstly, soccer players of a similar level of sport skills present similar levels of the behavior elements under consideration, and, secondly, the goal value as a dimension of deliberate behavior was best correlated with other elements - similarly to the motivational index of rivalry. The results achieved can be interpreted in the light of the assumed theories.